Religiosity in Islam as a Protective Mechanism against Criminal Temptation (American Journal of Islam and Society, 1994)
The goal of this paper is b examine the extent to which religiosity,within the Islamic context, can be viewed BS an effective mechanismagainst criminal temptation. To accomplish this, we will a) review thetheories and literatwe concerning the religion-crime relationship, b) discussthe meaning of the religiosity concept in order to highlight essentialfeatures of religiosity in Islam that make it a valuable force in crime controlwithin a Muslim society, and c) present a thorough discussion of certainelements of Islamic ideology that conshin criminal behavior.Theoretical AntecedenceThe relation of religion to other social phenomena has received agreat deal of attention from social scientists. Given the variations of theideological and philosophical backgrounds underlying most schools of SQcia1thought, theme is no single view of the impact of religion. For example,Ibn Khaldiin ([d. 14061 1981) views religion, through its effect onsocial cohesion and cooperation, as a primary factor in the rise and fallof Societies. Marx (Tucker 1978), in his analysis of capitalism, recognizesthe importance of religion as a control mechanism and considers itan effective instNment utilized by the bourgeois dass to maintain itsdominance over the proletariat. On the conttary, Weber (1958) views theentin= capitalist system as a by-product of Protestantism.But it is perhaps the functional theorists who highlight the impowceof religion on the creation and maintenance of social order. They considerreligion to be the basis and source of social values and norms by whichpeople are united and their behavior and activities are regulated murkheim1951). However, due to the increasingly secular nature of modem ...